PENGARUH SUSU IBU HAMIL TERHADAP EKSPRESI KALLIKREIN-RELATED PEPTIDASE-4 (KLK-4) PADA SEL AMELOBLAS DALAM TUMBUH KEMBANG GIGI - Samia, Salma; Christiono, Sandy; Sari, Rina Kartika (Odonto : Dental Journal, 2020)
Background: Tooth development during the embryonic period is a complex process that needs enough nutrition for the formation of healthy dental tissue. Kallikrein-related peptidase-4 (KLK-4) is a serine proteinase secreted by ameloblast during transition and maturation stages in the amelogenesis process which functions to degrade protein matrices so enamel could reach the final hardness. Pregnancy milk contains various nutrients that can increase KLK-4 expression of ameloblast cells in the tooth development. This study aims to determine the impact of pregnancy milk against the KLK-4 expression of ameloblast cell in the tooth development process.Method: 12 pregnant female mice (Mus Musculus L.) divided into control group (given sterile aquadest) and treatment group (given pregnancy milk + sterile aquadest) for 18 days then the tooth germ was taken. Samples were stained to see the KLK-4 expression. Data were analyzed using an Independent sample t-test.Result: Our study showed that the average amounts of KLK-4 expression in the treatment group are higher than the control group. Based on the Independent sample t-test statistic methods, there is a significant difference with the value of p=0,017.Conclusion: The pregnancy milk could influence the Kallikrein-related peptidase-4 (KLK-4) expression of ameloblast cell in the mice fetus’s tooth development.